Hard diffuse X-ray emission around the PSR J2032+4127: A pulsar wind nebula in the Cygnus OB2 association - Albacete Colombo, Juan Facundo (2020)
Fil: Albacete Colombo, Juan F. Universidad Nacional de Río Negro. Río Negro, Argentina.